Reconfiguring Women’s Religious Authority in Digital Islam: Hadith Reinterpretation on the TikTokAccount @sayyidah_nisa - Wiridtananda Widiastuti Melati; Mukhammad Zamzami; Ida Rochmawati; Rofhani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Women’s religious authority in Digital Islam is commonly associated with expanded religious participation and emancipatory agency, yet its ideological dimensions remain underexplored. This study examines how Hadith interpretation constructs women’s religious authority through the TikTok account @sayyidah_nisa, whose discourse reflects post-Hizbut Tahrir Indonesia (HTI) narratives. Using Norman Fairclough’s Critical Discourse Analysis, the study analyzes Hadith-based content and its discursive construction within Indonesia’s digital religious sphere. The findings demonstrate that Hadith interpretation functions not merely as theological interpretation but as a discursive mechanism that legitimizes complementary gender relations and reproduces conservative Islamist ideology. Digital affordances amplify this authority by extending the circulation and public legitimacy of ideological narratives beyond conventional religious institutions. The study suggests that women’s religious authority in Digital Islam constitutes an ideologically contingent discursive formation rather than an emancipatory phenomenon. This perspective extends Digital Islam scholarship by demonstrating how religious interpretation, ideological production, and digital mediation converge in shaping contemporary Muslim public discourse